Effects of formulation on flowability of selected herbal powders using compendial methods and powder flow analyser - Etti, Christopher Joseph; Yusof, Yus Aniza; Chin, Nyuk Ling; Mohd Tahir, Suraya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
This study was aimed at investigating the effects of formulation on flowability of selected herbal powders which include Labisia pumila, Ortosiphon stamineus, Eurycoma longifolia and Andrographis paniculata using compendial methods and a recently available powder flow analyser. The material properties such as moisture content, particles sizes, tap and bulk densities of the pure herbal powders and the formulated powders were measured to determine Carr index and Hausner ratio which were indices of the compendial methods. Cohesion index and caking strength were used as basis of flowability indicator using the powder flow analyser. The flowability of the herbal powders were improved when they were formulated into beverages mix by mixing each herbal powders with other ingredients like sugar and nondairy creamer before analyzed using both the compendial methods and powder flow analyser. Both methods of flowability measurements adopted in this work complemented each other in the understanding and characterization of powder flowability.